Rebamipide for Managing Dyspeptic Symptoms During Proton-Pump Inhibitor Washout Before Helicobacter pylori Testing: A Randomized, Double-Blind, Placebo-Controlled Trial - Suksai, Nottawan; Chueansuwan, Rachaneeporn; Yongsiri, Somchai; Witoon, Raweewan; Juttuporn, Anothai (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Persistent dyspeptic symptoms are common during the proton pump inhibitor (PPI) washout period before Helicobacter pylori (H. pylori) testing. However, the role of rebamipide in symptom management during this interval remains unclear. Materials and Methods: This double-blind, randomized controlled trial enrolled 65 patients with H. pylori–associated dyspepsia or gastritis, randomized (1:1) to receive rebamipide (100 mg 3 times daily) or placebo for 4 weeks, following a 14-day eradication regimen. The primary outcome was the proportion of responders achieving a ≥25% reduction in pain symptom scores on the Severity of Dyspepsia Assessment scale at week 6. Secondary outcomes included changes in pain symptoms, non-pain symptoms, and dyspepsia-related health scores, as well as eradication rates and safety. Results: All patients completed the trial. Although the proportion of responders was higher in the rebamipide group (18 patients, 56.3% vs. 13 patients, 39.4%), this difference was not statistically significant (P = .17). Scores for pain, non-pain, and dyspepsia-related health improved similarly in both groups. Eradication rates were comparable (87.5% vs. 90.0%), and no serious adverse events were reported. Conclusion: The responder rate was higher in the rebamipide group, but the difference did not reach statistical significance. The poten tial benefit of rebamipide as a rescue therapy during the PPI washout period before H. pylori testing warrants further investigation in larger trials. Cite this article as: Suksai N, Chueansuwan R, Yongsiri S, Witoon R, Juttuporn A. Rebamipide for managing dyspeptic symptoms during proton-pump inhibitor washout before Helicobacter pylori testing: A randomized, double-blind, placebo-controlled trial. Turk J Gastroenterol. Published online October 12, 2025. doi:10.5152/tjg.2025.25248.